Biomarkers Of CRP, IL-6, And D-dimer Covid-19 Patients That Are Giving Convalence Plasma Therapy – Literature Review - Rofiq, Ainul; Mahendra, Reza Hery; Bastiana; Tunjungsari, Yekti (Jurnal Medis Islam Internasional, 2021)
Background: Convalescent plasma therapy is the only antibody-based therapy used to treat COVID-19 Patients. The use of convalescent plasma therapy has been recommended by the Food and Drug Administration (FDA) as a therapy for COVID-19 patients (FDA in Asep, 2020). Several routine biomarker parameters used as indicators in the diagnosis of COVID-19 are CRP, IL-6 and D-Dimer. There was a change between the three biomarker values of CRP, IL-6, and D-Dimer between COVID-19 patients on convalescent plasma therapy and COVID-19 patients who did not receive convalescent plasma therapy. This review article is how effective the use of convalescent plasma as therapy for COVID-19 patients is by looking at changes in the biomarkers of CRP, IL-6 and D-Dimer in patients receiving convalescent plasma therapy. Methode: This literature review uses 3 fulltext articles obtained by combining keywords in an electronic database: Scopus, Cochrane Library, PubMed, and Google Scholar. Articles were eliminated using predefined inclusion and exclusion criteria, then analyzed systematically. The preparation of the discussion uses a systematic analysis based on the themes and topics of discussion obtained in the research article. Conclussions: There were changes in the biomarker values of CRP, IL-6 and D-Dimer in COVID-19 patients who received convalescent plasma therapy and COVID-19 patients who did not receive convalescent plasma therapy. Keywords: D-Dimer level, Interleukin 6 (IL-6) level, C-Reactive protein (CRP) level, plasma konvalesen, dan outcomes pasien COVID-19